Religiosity Mediation: Effects of Halal Labels and Halal Awareness on the Decision to Buy Halal Products in Non-Food Products - Assyarofi, Muhammad Rexsa; Wulandari, Fitri (Jurnal Ilmiah Ekonomi Islam, 2023)
Review and analyze the factors that influence the decision to purchase halal non-food products from halal labels and halal awareness. As well as the role of religiosity as a mediation that links halal labels and halal awareness to purchasing decisions for halal products. By using a purposive sampling technique, the number of samples in this study was 164, namely people in Solo Raya who had purchased non-halal food products. This study uses the SEM-SmartPLS analysis tool. The effect of halal labels on religiosity and purchasing decisions of halal products is not directly significant. However, the halal awareness variable has a direct, significant influence on product purchasing decisions and religiosity. The results show that religiosity has a significant influence on purchasing decisions for halal products. The mediating role of religiosity in the influence of halal labels on halal product decisions is not mediating. Meanwhile, the mediating role of religiosity on the influence of halal awareness on halal product decisions is partial mediation. The implication of this research is to provide an understanding of the relationship using latent constructs on the variables studied. Besides that, it is hoped that the halal industry players will find these findings useful in order to understand the urgency of aspects of halal non-food products which are specifically studied, namely halal awareness, halal labels, and religiosity in Muslim communities in Solo Raya, so that in the future they can design appropriate policies and strategies in capture market share that is increasingly potential and continues to grow.